Data from: Polygamy slows down population divergence in shorebirds - D'Urban Jackson, Josephine; Dos Remedios, Natalie; Maher, Kathryn H.; Zefania, Sama; Haig, Susan; Oyler-McCance, Sara; Blomqvist, Donald; Burke, Terry; Bruford, Mike W.; Szekely, Tamas; Küpper, Clemens; Bruford, Michael W. (2020)
Sexual selection may act as a promotor of speciation since divergent mate choice and competition for mates can rapidly lead to reproductive isolation. Alternatively, sexual selection may also retard speciation since polygamous individuals can access additional mates by increased breeding dispersal. High breeding dispersal should hence increase gene flow and reduce diversification in polygamous species. Here we test how polygamy predicts diversification in shorebirds using genetic differentiation and subspecies richness as proxies for population divergence. Examining microsatellite data from 79 populations in ten plover species (Genus: Charadrius) we found that polygamous species display significantly less genetic structure and weaker isolation-by-distance effects than monogamous species. Consistent with this result, a comparative analysis including 136 shorebird species showed significantly fewer subspecies for polygamous than for monogamous species. By contrast, migratory behaviour neither predicted genetic differentiation nor subspecies richness. Taken together, our results suggest that dispersal associated with polygamy may facilitate gene flow and limit population divergence. Therefore, intense sexual selection, as occurs in polygamous species, may act as a brake rather than an engine of speciation in shorebirds. We discuss alternative explanations for these results and call for further studies to understand the relationships between sexual selection, dispersal and diversification. Polygamy slows diversification in shorebirds_rawdataThis file contains all of the raw microsatellite data for ten species of plover. Kittlitz's plover and white-fronted plover are divided into two datasets which represent 1) mainland African populations and 2) Madagascan populations. Details of the microsatellite markers and PCR conditions can be found in the paper. Killdeer plover has one marker identified as having a high estimate of null alleles, this is marked in grey shading.shorebird_subspeciesThis file contains breeding ...